Epidemiologi dan Diagnosis Kasus Atypical Trypanosomiasis Pada Manusia dan Rodensia - Saulimita Risti; Nurhadi Eko Firmansyah; Heri Wibowo (Fakultas Kedokteran Universitas Riau, 2026)
Atypical human trypanosomiasis (AHT) is a zoonotic disease caused by animal trypanosomes, one of which is Trypanosoma lewisi, a parasite that naturally infects rodents and can be transmitted to humans. Cases of AHT have been reported in several Asian and African countries, particularly affecting infants and immunocompromised individuals. However, AHT remains underreported due to nonspecific clinical manifestations, limited public awareness, and the lack of sensitive diagnostic methods. This narrative review synthesizes recent scientific evidence on AHT caused byT. lewisi. A systematic literature search was conducted using PubMed, ScienceDirect, and Google Scholar, focusing on full-text articles published between 2016 and 2026. Relevant studies were qualitatively analyzed to address epidemiological distribution, zoonotic transmission mechanisms, and diagnostic approaches and their limitations.The review results indicate that T. lewisi is widely distributed among rodent populations and has the potential to infect humans. Microscopic examination remains the most commonly used diagnostic method but shows low sensitivity, particularly in cases of low parasitemia. In contrast, molecular methods such as PCR and LAMP demonstrate higher sensitivity and specificity, while serological methods such as ELISA show potential for epidemiological surveillance, although further standardization is required. In conclusion, AHT caused by T. lewisi is a neglected zoonotic disease that warrants increased public health attention through strengthened surveillance, improved diagnostic capacity, and the implementation of a One Health approach.